Out on the pull: how small firms are making themselves sexy with new online promotion techniques. (16th July 2008) - Harris, Lisa; Rae, Alan; Grewal, Simran
We examine the range of online marketing options that are now available to small businesses and demonstrate how the sands are shifting from 'push' communications based on e-mail, to 'pull' technologies such as Really Simple Syndication (RSS), where customers choose precisely which promotional messages to receive and which to reject. We draw upon the early results of an ongoing research project investigating how the 'early adopter' small firms are using these new technologies. We discuss the problems faced by small businesses in promoting themselves on limited budgets and we consider how the so-called 'Web 2.0' technologies, such as RSS, social networks, video and blogs are transforming the online marketing landscape for the proactive firms in our study. We conclude that the 'early adopters' we profiled are starting to develop expertise and fluency in how these tools can be used, successfully promoting their businesses and generating competitive advantage by 'punching above their weight' online.